Immunofluorescence Staining of Paraffin Sections Step by Step - Zaqout, Sami; Becker, Lena-Luise; Kaindl, Angela M. (Frontiers in Neuroanatomy, 2020)
Immunofluorescence staining is the most frequently applied technique to detect and visualize various molecules in biological samples. Many protocols can be found in the literature and the websites of commercial antibody producers. This can result in a time-consuming and costly methodical work to establish “simple” antibody staining. We here summarize in a stepwise manner an easy-to-follow immunofluorescence staining protocol with an improved specific fluorescent signal and a reduced background and non-specific binding signal. This will help scientists to save time, effort, and antibody costs during the application of such a valuable technique.